Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Chen, Yi-Sheng; Wu, Hui-Chung; Wang, Chiung-Mei; Lin, Chia-Chun; Chen, Yi-Ting; Jhong, Yu-Jyun; Yanagida, Fujitoshi (Folia microbiologica, 2013)
Lactobacillus pobuzihii is a novel species which has been previously found in pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan. However, the lactic acid bacteria (LAB) microflora in pobuzihi has not been studied in detail. In this study, LAB from pobuzihi were isolated, identified, and characterized. A total of 196 LAB were isolated; 79 cultures were isolated from the sample collected from a manufacturing factory, 38 from pobuzihi samples collected from 4 different markets, and 79 from 2 fresh cummingcordia samples. These isolates were characterized phenotypically and then divided into eight groups (A to H) by restriction fragment length polymorphism analysis and sequencing of 16S ribosomal DNA. Lactobacillus plantarum was the most abundant LAB found in most samples during the fermentation of pobuzihi. On the other hand, Enterococcus casseliflavus and Weissella cibaria were, respectively, the major species found in the two fresh cummingcordia samples. A potential novel species or subspecies of lactococcal strain was found. In addition, seven L. plantarum and five W. cibaria strains showed inhibitory activity against the indicator strain Lactobacillus sakei JCM 1157(T). This is the first report describing the distribution and varieties of LAB existing in the pobuzihi during its fermentation process and the final product on the market.
Keywords: Food Microbiology; biodiverzita; ribozomální DNA; DNA, Ribosomal; polymorfismus délky restrikčních fragmentů; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; Molecular Sequence Data; RNA ribozomální 16S; fermentace; Polymorphism, Restriction Fragment Length; potravinářská mikrobiologie; molekulární sekvence - údaje; Biodiversity; Fermentation; Sequence Analysis, DNA; Lactobacillales; sekvenční analýza DNA; Taiwan